DEVELOPMENT AND VALIDATION OF STABILITY INDICATING REVERSED PHASE HIGH PERFORMANCE LIQUID CHROMATOGRAPHIC METHOD FOR THE DETERMINATION OF RELATED SUBSTANCES IN FAMPRIDINE DRUG SUBSTANCE AND TABLET DOSAGE FORMS - C, Babu; Rao Kl, Narasimha; N, Devanna; Kvn, Suresh Reddy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The objective of this method is to develop a stability-indicating reversed phase high performance liquid chromatographic method for the quantification of related substances in the drug substance and tablet dosage form of Fampridine. Methods: Inertsil ODS 3V, (150 mm Ã— 4.6 mm, 5 Î¼m particle size) column was used for the separation of analytes. Mobile phase A was prepared by dissolving 6.8 g of potassium dihydrogen orthophosphate (0.05 mol) and 1 g of 1-octane sulfonic acid into a 1000 ml of water, pH was adjusted to 4.0Â±0.05 with diluted orthophosphoric acid. Mobile phase B was prepared by mixing the above phosphate buffer (pH 4.0) and acetonitrile in 20:80 (% v/v). Gradient mode was used with the flow rate of 1.0 ml/minutes, and the peaks were monitored at 260 nm. Results: Linearity results showed that the correlation coefficient (r2) is >0.995 for individual active drug substances as well as their related substances in the range of limit of quantification to 150% of the specification concentration (0.5% with respect to sample concentration of 0.4 mg/ml). Accuracy of the method was established with their recovery values in the range of 98.5-104.5% with the % RSD not more than 1.7%. The method was proved by highly precise (% RSD of intra-day and inter-day study was not more than 4.3%) and more robust. Conclusion: Present method is able to separate two related compounds with each other and with the main drug substance with the resolution more than 2.0. The test standard solution and test solution were found to be stable in diluent up to 24 hrs. The mass balance of forced degradation of formulations is close to 99% made this method as a stability indicating method.